Susceptibility to Infections During Acute Liver Injury Depends on Transient Disruption of Liver Macrophage Niche - Lopes, Mateus Eustáquio; Nakagaki, Brenda Naemi; Mattos, Matheus Silvério; Campolina-Silva, Gabriel Henrique; Meira, Raquel de Oliveira; Paixão, Pierre Henrique de Menezes; Oliveira, André Gustavo; Faustino, Lucas D.; Gonçalves, Ricardo; Menezes, Gustavo Batista (Frontiers in Immunology, 2022)
Kupffer cells are the primary liver resident immune cell responsible for the liver firewall function, including clearance of bacterial infection from the circulation, as they are strategically positioned inside the liver sinusoid with intimate contact with the blood. Disruption in the tissue-resident macrophage niche, such as in Kupffer cells, can lead to a window of susceptibility to systemic infections, which represents a significant cause of mortality in patients with acetaminophen (APAP) overdose-induced acute liver injury (ALI). However, how Kupffer cell niche disruption increases susceptibility to systemic infections in ALI is not fully understood. Using a mouse model of ALI induced by APAP overdose, we found that Kupffer cells upregulated the apoptotic cell death program and were markedly reduced in the necrotic areas during the early stages of ALI, opening the niche for the infiltration of neutrophils and monocyte subsets. In addition, during the resolution phase of ALI, the remaining tissue macrophages with a Kupffer cell morphology were observed forming replicating cell clusters closer to necrotic areas devoid of Kupffer cells. Interestingly, mice with APAP-induced liver injury were still susceptible to infections despite the dual cellular input of circulating monocytes and proliferation of remaining Kupffer cells in the damaged liver. Therapy with bone marrow-derived macrophages (BMDM) was shown to be effective in occupying the niche devoid of Kupffer cells following APAP-induced ALI. The rapid BMDM migration to the liver and their positioning within necrotic areas enhanced the healing of the tissue and restored the liver firewall function after BMDM therapy. Therefore, we showed that disruption in the Kupffer cell niche and its impaired function during acute liver injury are key factors for the susceptibility to systemic bacterial infections. In addition, modulation of the liver macrophage niche was shown to be a promising therapeutic strategy for liver injuries that reduce the Kupffer cell number and compromise the organ function.